Alteraciones anatomo patológicas macroscópicas del aparato reproductor - Yunda Guacho, Martha Elena (2008)
This research was conducted in the canton of municipal Camal Machala, from January 23 until April 3 of 2008, with the purpose of determining the presence of anatomical abnormalities – pathological reproductive tract in cattle there fishing, the following three objectives: 1. Establish by observation, palpation, and court, pathological changes in the reproductive tract of cattle slaughtered, 2.- To determine the presence percentage of affected organs according to their orogin, age, sex and race, 3. Prepare an estímate of potential economic losses by confiscation of reproductive organs due to the presence of pathological changes. To carry out this work was inspected a total of 903 animals, over a period of 71 days. MOst animals that fishing came from the provinces of Zamora Chinchipe, Loja and El Oro, the cantons where it came from animals in the province were Machala, Santa Rosa, Atahualpa, El Guabo, Marcabeli. The results found that the alterations that were found most frequently were: mastitis (1.21%), ovarían cysts (0.88%), metritis (0.33%) and pyometra (0.22%). Losses by confiscating bodies amounted to $23.8 resulting from the seizure of 14 kg, udder.